Musical Cryptography: Codes, Ciphers, Form, and Function - Thompson, Benjamin (2024)
This thesis investigates the conception, historical development, and function of musical cryptography. Musicologists such as David Løberg Code, Eric Sams, Roy Howat, and Helen Elizabeth Rudeforth will provide the framework for cipher and code-based study, while Johannes Kepler, Mihail Cocos, and Shawn Fowers provide the framework for study of the relationship between music and mathematics. By clarifying the origins of codification and examining the musical applications of cryptographic practice, this thesis hopes to establish the significance of musical cryptology, not as supplementary to other analyses, but as an autonomous branch of musicology.